Regional development and non-territorial policies: meaningful evidence of a neglected relation - Paulo Miguel Madeira; Mário Vale; Jorge Malheiros (Regional Studies, Regional Science)
In the period after the 2008 financial crisis, the European Union and Brazil experienced, respectively, periods of regional divergence and convergence. The research developed in these two territories brings new evidence on the importance of non-territorial policies, that worked as indirect regional policy, for these trajectories. In the case of the EU, (direct) regional policy was not strong enough to counteract more non-territorial policies that acted in favour of divergence. In the case of Brazil, the absence of a relevant direct regional policy did not prevent convergence, since the government adopted a set of non-territorial sectoral policies that functioned as indirect regional policy. This is particularly relevant in the current European context, where prolonged social and economic stagnation or decline in many regions has been the source of discontent that is expressed electorally.